Adaptive extended Kalman filter and laser link acquisition in the detection of gravitational waves in space - Yang, Jinke; Xie, Yong; Fan, Yidi; Wang, Pengcheng; Wang, Xue; Cui, Zhao; Jia, Jianjun; Tang, Yucheng; Lau, Yun Kau (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionEstablishing stable laser links in triangular spacecraft constellations for gravitational wave detection is challenging due to large initial pointing uncertainties and the limitations of conventional acquisition schemes.MethodsWe propose an alternative acquisition scheme that replaces the wide-field CCD camera with an adaptive extended Kalman filter (AEKF) integrated into the point-ahead angle mechanism (PAAM). The scheme employs a quadrant photodetector (QPD) based on differential power sensing (DPS), which provides a higher dynamic range than differential wavefront sensing (DWS).ResultsBy integrating coarse and fine acquisition into a single control loop, the payload structure of the acquisition, tracking, and pointing (ATP) system is simplified. Numerical simulations using a colored measurement noise model, representative of on-orbit conditions, show that the AEKF effectively predicts the point-ahead angle (PAA) and significantly reduces the initial uncertainty region, even under worst-case spacecraft navigation errors.DiscussionThe proposed scheme avoids CCD-induced heating issues, enhances robustness against navigation errors, and offers a simplified yet efficient approach for deep-space laser link acquisition in gravitational wave detection missions.